ANALISIS PUTUSAN PENGADILAN NEGERI REMBANG NOMOR 6/PDT.G/2018/PN.RBG MENGENAI PENGUASAAN TANAH TANPA HAK - Christhalia Noveldy Tanjaya; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
Land acquisition is a relationship between individual or a  public group or a legal entity which related with domination or usage of the land. Meanwhile, land without rights is the domination exercised by a person or legal entity to enjoy land that is not his own by occupying the land or constructing a building on the land without the knowledge and permission of the legal owner of the land. This research aims to determine land acquisition according to the UUPA and to analyze land acquisition without rights performed by Muin and Tasi in the Rembang District Court Decision Number 6 / Pdt.G / 2018 / PN.Rbg. The type of research in this  papers is normative legal research. The approach of this research is using statutory research. The nature of this research uses descriptive analytics. The types of data used are divided into primary and secondary data which are further divided into primary, secondary, and tertiary legal entities.. The data collection technique uses literature study. Qualitative data analysis techniques. The conclusion of this study is that the author agrees with the judge's decision which states that Muin and Tasi's actions are against the law and states that Suparmanto is the rightful owner of the land and building, but the author does not agree with the judge's decision which rejects the claim of damages applied by the Plaintiff.